Stochastic Finite-Time H∞ Performance Analysis of Continuous-Time Systems with Random Abrupt Changes - Bing Wang (Abstract and Applied Analysis)
The problem of H∞ control performance analysis of continuous-time systems with random abrupt changes is concerned in this paper. By employing an augmented multiple mode-dependent Lyapunov-Krasovskii functional and using some integral inequalities, new sufficient conditions are obtained relating to finite-time bounded and an H∞ performance index. The finite-time H∞ control performance problem is solved and desired controller is given to ensure the system trajectory stays within a prescribed bound during a given time interval. At last, two numerical examples are provided to show that our results are less conservative than the existing ones.